1988
DOI: 10.1136/bmj.297.6657.1169
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and imagery in the treatment of breast cancer.

Abstract: of local recurrence is three times that of ductal carcinoma.The determination of those who selected mastectomy is interesting. In answer to the possible criticism that we may have influenced the patients to choose this treatment, we used a technique that biased the discussion towards conservation, which in the end was selected by fewer women. Bias towards conservation was also often applied by relatives and friends. Well meaning relatives may find it difficult to believe that mastectomy is genuinely the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
5

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 25 publications
3
58
0
5
Order By: Relevance
“…15,16 Application of CAM-based approaches was reported as being beneficial in cancer patients in chemotherapy-associated nausea and vomiting, 17 pain, 18 fatigue, 19 relaxation, 20,21 and anxiety and mood disturbances (for a review, see Deng and Cassileth 22 ). Furthermore, prominent cancer centers, such as M.D.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Application of CAM-based approaches was reported as being beneficial in cancer patients in chemotherapy-associated nausea and vomiting, 17 pain, 18 fatigue, 19 relaxation, 20,21 and anxiety and mood disturbances (for a review, see Deng and Cassileth 22 ). Furthermore, prominent cancer centers, such as M.D.…”
Section: Discussionmentioning
confidence: 99%
“…Hypnosis and relaxation techniques Cassileth,Deng 85 are often used by conventional practitioners, such as clinical psychologists. Several randomized trials have shown effects of hypnosis on both procedural and malignant pain [84,85] and on anxiety, depression, and mood in newly diagnosed cancer patients [86][87][88]. Trials also have generally found hypnosis and relaxation training to be beneficial against chemotherapy-induced nausea in adults [89,90], although some studies found no differences between groups [91].…”
Section: Helpful Complementary Therapiesmentioning
confidence: 99%
“…Inclusion of two (Gordon et al, 1980;Bridge et al, 1988) might have reduced the mean effect size for anxiety (see second last column Table 2). …”
Section: Anxiety Meta-analysismentioning
confidence: 99%
“…Figure 6) The ten excluded studies are summarized in Table 2. Inclusion of four (Farash, 1977;Gordon et al, 1980;Bridge et al, 1988;Burton and Parker, 1988) would probably have reduced the mean effect size, while inclusion of one (Watson et al, 1988) would have increased it.…”
Section: Depression Meta-analysismentioning
confidence: 99%